Leukocyte integrin Mac-1 regulates thrombosis via interaction with platelet GPIbα - Yunmei Wang (Nature Portfolio, 2017)
The binding of the leukocyte integrin Mac1 to the platelet receptor GPIbα is important for the physiological response to tissue injury. Here the authors show that this interaction also regulates thrombosis, without influencing bleeding time, which may provide clues for the development of new anti-thrombotic drugs.